1998
DOI: 10.1128/aem.64.11.4333-4339.1998
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Nonthermophilic Members of the Kingdom Crenarchaeota and Their Diversity and Abundance in Soils

Abstract: Within the last several years, molecular techniques have uncovered numerous 16S rRNA gene (rDNA) sequences which represent a unique and globally distributed lineage of the kingdom Crenarchaeotathat is phylogenetically distinct from currently characterized crenarchaeotal species. rDNA sequences of members of this novel crenarchaeotal group have been recovered from low- to moderate-temperature environments (−1.5 to 32°C), in contrast to the high-temperature environments (temperature, >80°C) required for growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
1
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(110 citation statements)
references
References 36 publications
5
102
1
2
Order By: Relevance
“…Nevertheless, most soil archaeal sequences fall within the 1.1b lineage (e.g. Buckley et al, 1998;Ochsenreiter et al, 2003), and most of those detected here may fall within this lineage. Therefore, 16S rRNA-based analysis may target largely amoA-possessing organisms if ammonia monooxygenase is possessed by organisms throughout the lineage.…”
Section: Soil Ph and Crenarchaeal Phylogenymentioning
confidence: 75%
“…Nevertheless, most soil archaeal sequences fall within the 1.1b lineage (e.g. Buckley et al, 1998;Ochsenreiter et al, 2003), and most of those detected here may fall within this lineage. Therefore, 16S rRNA-based analysis may target largely amoA-possessing organisms if ammonia monooxygenase is possessed by organisms throughout the lineage.…”
Section: Soil Ph and Crenarchaeal Phylogenymentioning
confidence: 75%
“…Organisms belonging to the largely non-thermophilic 'Group 1' Crenarchaeota lineage appear to be ubiquitous in soil systems including grassland, forest, agricultural and rice field soils (e.g. Bintrim et al ., 1997;Jurgens et al ., 1997;Buckley et al ., 1998;Großkopf et al ., 1998;Nicol et al ., 2003a) and may be dominant over euryarchaeal populations in grassland soils (Nicol et al ., 2003b). Despite an increasing understanding of crenarchaeal diversity in the environment, little is known about the drivers of crenarchaeal diversity and their ecological functioning in soil systems (Nicol et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Sandaa et al ., 1999;Nicol et al ., 2003a) and their apparent ubiquity but reduced complexity in comparison with bacterial communities make crenarchaea a useful target group when making comparisons between different environmental samples. Crenarchaea have been reported to constitute a significant proportion of soil prokaryotes ranging from 0.16% to 3% of 16S rRNA genes (Ochsenreiter et al ., 2003) and approximately 1% of hybridized whole cells (Sandaa et al ., 1999) or extracted 16S rRNA (Buckley et al ., 1998). Several studies have indicated that soil crenarchaea may have a specific association with plant roots (Großkopf et al ., 1998;Simon et al ., 2000;Chelius and Triplett, 2001) and crenarchaea may therefore play an important role in the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative estimates have demonstrated the significant occurrence of non-thermophilic crenarchaeota in marine habitats (Massana et al ., 1997;Karner et al ., 2001), in freshwater sediments (McGregor et al ., 1997) and in soil (Buckley et al ., 1998;T. Ochsenreiter and C. Schleper, in preparation).…”
Section: Introductionmentioning
confidence: 99%